DELAY OF ELECTIVE OPERATIONS IN AWAL BROS PANAM PEKANBARU HOSPITAL JANUARI-APRIL 2018 - Muhammad Eriex Fornando Suka; Adik Wibowo (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: Competition between hospitals is increasing, for thathospital should maintain the quality of service and patient satisfaction. Hospitals should have innovation targets for cost effectiveness and productivity without compromising patient safety and quality of care. Operation delays are one barrier to optimal patient flow, increasing patient anxiety, affecting interprofessional teamwork across the medical discipline and ultimately putting patients at risk of safety. Methods: This research is descriptive research with a quantitative approach, data obtained from the surgery room register and interview which then grouped and analyzed. Results: There was an elective delay in surgery of 38%, with the highest cause being the staffing factor of 81%, the highest percentage of delays was plastic surgery 61% of total surgery performed, The highest number of delays occurred in Urology that is 213 cases. Conclusions: To reduce the delay required clear rules in the event of delays and rules of payment based on performance services, which is timeliness of attendance elective operation schedule is one of the assessment tools, and scheduling operations outside the time outpatient service.